Hidden diversity in sardines: genetic and morphological evidence for cryptic species in the goldstripe sardinella, Sardinella gibbosa (Bleeker, 1849). - Rey C Thomas (Public Library of Science (PLoS), 2014)
Cryptic species continue to be uncovered in many fish taxa, posing challenges for fisheries conservation and management. In Sardinella gibbosa, previous investigations revealed subtle intra-species variations, resulting in numerous synonyms and a controversial taxonomy for this sardine. Here, we tested for cryptic diversity within S. gibbosa using genetic data from two mitochondrial and one nuclear gene regions of 248 individuals of S. gibbosa, collected from eight locations across the Philippine archipelago. Deep genetic divergence and subsequent clustering was consistent across both mitochondrial and nuclear markers. Clade distribution is geographically limited: Clade 1 is widely distributed in the central Philippines, while Clade 2 is limited to the northernmost sampling site. In addition, morphometric analyses revealed a unique head shape that characterized each genetic clade. Hence, both genetic and morphological evidence strongly suggests a hidden diversity within this common and commercially-important sardine.